Desain Pembelajaran Berbasis Case Study Pada Mata Kuliah Pendidikan IPS - Piki Setri Pernantah; Khairiyah Khadijah; Mirza Hardian; Bedriati Ibrahim; Masro Fatil Khasanah (Institut Agama Islam Negeri Bengkulu, 2022)
In universities in the social sciences and education clusters, the social studies education course is one of the important compulsory courses to be taught. In the Social Studies Education course, it is hoped that it can contribute to growing student national awareness, social insight, social spirit, and social sensitivity so as to foster good social interaction in social life. In the learning process, social studies education must prioritize active learning. The case study learning method can make students better understand the material and master more contextual learning in accordance with the semester learning design that has been prepared. In addition, students will be more responsible for the problems given to be solved. This article aims to: 1) describe the importance of case study-based social studies courses; 2) design an example of a learning scenario with the case study method in the Social Studies Education course.